24-hour intragastric acidity and nocturnal acid secretion in patients with duodenal ulcer during oral administration of cimetidine and atropine. Issue 2 (February 1977) - Pounder, R E; Hunt, R H; Vincent, S H; Milton-Thompson, G J; Misiewicz, J J
Abstract : Cimetidine markedly inhibits gastric acid secretion, but from the therapeutic point of view it is important to know whether concurrent treatment with an anticholinergic increases its effect. This possibility has been investigated by measuring the 24 h intragastric acidity and nocturnal output of acid in four duodenal ulcer patients, each receiving on separate occasions cimetidine 1 g/day and placebo, atropine 2-4 mg/day and placebo, cimetidine and atropine, or two placebos. Cimetidine alone decreased mean hourly hydrogen ion activity by 63% of control values, decreased mean hourly hydrogen ion concentration (total acid) by 41%, inhibited nocturnal acid secretion by 83% and resulted in half the nocturnal samples being anacidic. Atropine alone had no effect when compared with control and combined treatment with both drugs was not superior to cimetidine alone. Atropine did not affect the absorption or urinary excretion of cimetidine. Fasting serum gastrin concentrations were not changed by any of the treatments. At the doses studied, the combination of cimetidine with an anticholinergic appears to offer no advantages over treatment with the H2-antagonist alone. Cimetidine is the only potent anti-secretory drug that does not cause acute side-effects and this important advantage would be lost if it were given with a maximal dose of an anticholinergic.